1) (y - xz)p + (yz - x)q = (x + y)(x - y)
Given equation is "(y - xz)p + (yz - x)q = (x + y)(x - y)"
Comparing with the standard equation, "Pp+Qq=R"
"\\frac{dx}{P}=\\frac{dy}{Q}=\\frac{dz}{R}"
Equation will be,
"\\frac{dx}{y-xz}=\\frac{dy}{yz-x}=\\frac{dz}{(x+y)(x-y)} = \\frac{xdx+ydy+zdz}{0} = \\frac{ydx+xdy}{y^2-x^2}"
"\\frac{dx}{y-xz}=\\frac{dy}{yz-x}=\\frac{dz}{x^2-y^2} = \\frac{xdx+ydy+zdz}{0} = \\frac{ydx+xdy}{y^2-x^2}"
"{xdx+ydy+zdz} = {0}"
solving it,
"x^2+y^2+z^2=c_1" (1)
Equation (1) is the solution of the given differential equation
Taking (iii) and last part,
"\\frac{dz}{x^2-y^2} = \\frac{ydx+xdy}{y^2-x^2}"
"dz = -ydx-xdy"
Integrating both sides,
"z = -xy + c_2" (2)
"z +xy = c_2"
Equations (1) and (2) are solutions to the equation.
The general solution of the differential equation will be
"\\phi(x^2+y^2+z^2,z+xy)=0."
Comments
Leave a comment